Seasonal dry matter production, botanical composition and forage quality of kikuyu over-sown with annual or perennial ryegrass - van der Colf, Janke; Botha, Philip R; Meeske, Robin; Truter, Wayne F (African journal of range & forage science, 2015)
The seasonal growth and low forage quality of kikuyu restrict milk production. The aim of this study was to determine the yield and nutritional value of irrigated kikuyu over-sown with perennial, Italian or Westerwolds ryegrass grazed by dairy cows. The three pasture systems reached optimum growth during different months and seasons. Lowest growth rates occurred during winter. Peak growth rates occurred during spring for the Italian ryegrass-kikuyu, summer for the Westerwolds ryegrass-kikuyu, and late spring and early summer for perennial ryegrass-kikuyu pasture. All three pasture systems had similar total annual dry matter yields (kilograms dry matter [DM] per hectare) during year 1, but the perennial ryegrass-kikuyu pasture achieved a higher annual DM yield during year 2. As kikuyu density increased in kikuyu-ryegrass pastures from winter to summer, the DM and neutral detergent fibre content increased, whereas the metabolisable energy content decreased. All three treatments were deficient in calcium during all seasons and in phosphorus during summer and autumn as a pasture for high-producing dairy cows.